2023
DOI: 10.1021/jacs.3c01146
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Unexpected Modulator-CO2 Dynamics within a Zirconium Metal–Organic Framework

Abstract: Carbon capture, storage, and utilization (CCSU) represents an opportunity to mitigate carbon emissions that drive global anthropogenic climate change. Promising materials for CCSU through gas adsorption have been developed by leveraging the porosity, stability, and tunability of extended crystalline coordination polymers called metal−organic frameworks (MOFs). While the development of these frameworks has yielded highly effective CO 2 sorbents, an in-depth understanding of the properties of MOF pores that lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 50 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…The MB-pol and MB-nrg , data-driven many-body PEFs were used to model the H 2 O and CO 2 molecules, respectively. Previous studies have demonstrated that these PEFs are transferable across the different phases of pure H 2 O , and CO 2 , , able to reproduce the properties of H 2 O and CO 2 mixtures, and accurately predict the behavior of H 2 O ,, and CO 2 molecules in MOFs.…”
Section: Methodsmentioning
confidence: 99%
“…The MB-pol and MB-nrg , data-driven many-body PEFs were used to model the H 2 O and CO 2 molecules, respectively. Previous studies have demonstrated that these PEFs are transferable across the different phases of pure H 2 O , and CO 2 , , able to reproduce the properties of H 2 O and CO 2 mixtures, and accurately predict the behavior of H 2 O ,, and CO 2 molecules in MOFs.…”
Section: Methodsmentioning
confidence: 99%
“…Note that such type V isotherms for SO 2 sorption have been computationally predicted in other MOF materials with simple nonfunctionalized linkers and exceptionally high pore volumes such as MOF-177 and IRMOF series, , which apparently is not the case for Zr-TPA-FA and Zr-TPA-HAc. Inspired by our recent work that discovered the unexpected modulator–CO 2 dynamics in Zr-MOFs both experimentally and computationally, which unveil the important role of the capping modulator in enhancing CO 2 binding within the pores, we hypothesize that the lability differences of the capping modulator could also remarkably influence the SO 2 sorption performances of Zr-TPA variants through distinct modulator–node dynamics (Figure a). Therefore, we performed density functional theory (DFT) calculations on cluster models of the two representative MOFs of Zr-TPA-FA and Zr-TPA-TFA to assess the preferential physical and chemical binding sites of SO 2 and probe the experimentally observed modulator effects on sorption (computational details in Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Defect engineering, originating from missing building blocks in the framework, is considered an efficient solution to provide more coordinatively unsaturated sites, thus improving CO 2 separation performance. 32,33 One interesting example is MOF-808, 34 a typical zirconium-based MOF, which allows for easy access to open zirconium sites due to minimized steric inhibition. It exhibited special dynamic behaviour in the pores of variants of MOF-808-X with different capping modulators (formate, acetate, and trifluoroacetate, termed FA, AA, and TFA), affording open zirconium sites for direct chemisorption of CO 2 .…”
Section: Porous Materials With Functional Sitesmentioning
confidence: 99%